Exorcising translation towards an intercivilizational turn - Robinson, Douglas 1954- (Literatures, cultures, translation, 2017)
A major new work in translation studies and comparative literature, looking at the tensions and relations between western and eastern culture and literature, by a pioneering scholar in the field"